Studi Komparasi Standar Pengujian Statis Pada Kereta dengan Penggerak Sendiri Berkecepatan Normal - Ardiatomo, Prabowo; Malkhamah, Siti; Wibisono, M. Arif (Pusat Penelitian dan Pengembangan Masyarakat (P3M), Politeknik Negeri Padang, 2024)
Railways are a unified system consisting of infrastructure, rolling stock and human resources as well as norms, criteria, requirements and procedures for the operation of railways. Every rolling stock operating in Indonesia must undergo first testing and periodic testing to ensure its operational feasibility. From data Directorate General of Railways in 2015-2021, it can be seen that the realization of the eligibility certificate for rolling stock has not been optimal, so that regulatory support is needed to maximize the performance of rolling stock testers. This study aims to compare the standards for static testing of temperature and air circulation on self-propelled coach applied in Indonesia and Europe. Based on a comparison of the static testing standards in Indonesia against the static testing standards in Europe, it is hoped that recommendations for improvement from the current static testing standards will be obtained. The method used in this research is qualitative method. Analysis of the data used using descriptive and comparative analysis. The results of the study comparison of the standard static testing of temperature and air circulation of self-propelled trains that apply in Indonesia and Europe, overall there are differences in the items tested, the value of acceptance and testing procedures. There are equal only in the item tested on air circulation static test. Temperature testing requires the addition of test items and improvements in the implementation of test procedures. Air circulation static testing needs improvement in the implementation of testing procedures.